2021
DOI: 10.1093/ehjcr/ytab140
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent massive pulmonary embolism following catheter directed thrombolysis in a 21-year-old with COVID-19: a case report

Abstract: Background Coronavirus Disease-2019 (COVID-19) has been associated with increased incidence of pulmonary embolism (PE), even among patients at low risk for venous thrombo-embolic (VTE) events. Case summary We present the case of a 21-year-old male, with no previous medical history, who presented with cough, fevers, shortness of breath, pleuritic chest pain, and 1 day of dizziness with near syncope as well as acutely worsened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Acute COVID-19 infections have been associated with hypercoagulability and thromboembolic complications ( 56 ). There is a report of an adolescent successfully utilizing dual CDT for segmental and subsegmental PE in the setting of acute COVID-19 as well as a 21-year-old with recurrent PE undergoing successful CDT for bilateral PE ( 12 , 57 ). Yet, in adolescents and children, MIS-C has been shown to have a higher TE incidence than acute COVID-19 infections ( 58 ).…”
Section: Thrombolysis In Childrenmentioning
confidence: 99%
“…Acute COVID-19 infections have been associated with hypercoagulability and thromboembolic complications ( 56 ). There is a report of an adolescent successfully utilizing dual CDT for segmental and subsegmental PE in the setting of acute COVID-19 as well as a 21-year-old with recurrent PE undergoing successful CDT for bilateral PE ( 12 , 57 ). Yet, in adolescents and children, MIS-C has been shown to have a higher TE incidence than acute COVID-19 infections ( 58 ).…”
Section: Thrombolysis In Childrenmentioning
confidence: 99%
“…Cases of cerebral infarcts as well as venous and cardiac thrombosis have been reported in children requiring extracorporeal membrane oxygenation (ECMO) for COVID-19 or MIS-C [31 ▪ ,37 ▪ ,38–40]. Adult studies have reported an increased risk of venous, arterial, and circuit thrombosis in patients requiring ECMO for COVID-19 [41,42].…”
Section: Thrombotic Events In Children With Coronavirus Disease 2019 ...mentioning
confidence: 99%